Machine-learning approaches to exoplanet transit detection and candidate validation in wide-field ground-based surveys. Issue 4 (22nd November 2018) - Schanche, N; Cameron, A Collier; Hébrard, G; Nielsen, L; Triaud, A H M J; Almenara, J M; Alsubai, K A; Anderson, D R; Armstrong, D J; Barros, S C C; Bouchy, F; Boumis, P; et al.
Abstract: Since the start of the Wide-angle Search for Planets (WASP) program, more than 160 transiting exoplanets have been discovered in the WASP data. In the past, possible transit-like events identified by the WASP pipeline have been vetted by human inspection to eliminate false alarms and obvious false positives. The goal of this paper is to assess the effectiveness of machine learning as a fast, automated, and reliable means of performing the same functions on ground-based wide-field transit-survey data without human intervention. To this end, we have created training and test data sets made up of stellar light curves showing a variety of signal types including planetary transits, eclipsing binaries, variable stars, and non-periodic signals. We use a combination of machine-learning methods including Random Forest Classifiers (RFCs) and convolutional neural networks (CNNs) to distinguish between the different types of signals. The final algorithms correctly identify planets in the test data ∼90 per cent of the time, although each method on its own has a significant fraction of false positives. We find that in practice, a combination of different methods offers the best approach to identifying the most promising exoplanet transit candidates in data from WASP, and by extension similar transit surveys.